Regulation of transforming growth factor-beta1 by circANKS1B/miR-515-5p affects the metastatic potential and cisplatin resistance in oral squamous cell carcinoma. Issue 2 (20th December 2021) - Yan, Jiawei; Xu, Hongyan
ABSTRACT: Oral squamous cell carcinoma (OSCC) is the most common oral cancer, with an increasing worldwide incidence and a worsening prognosis. Emerging evidence confirms that circular RNAs (circRNAs) play a critical role in tumor progression via sponging miRNAs. A previous study substantiated the function of circANKS1B in several cancers. However, its role in OSCC remains unclear. This study revealed the high expression of circANKS1B in OSCC tissues and cells. Moreover, the expression level of circANKS1B was highly positively correlated with the expression of transforming growth factor-beta1 (TGF-β1) in OSCC tissues. Additionally, overexpression of circANKS1B enhanced the protein expression of TGF-β1 in OSCC cells, while its inhibition reduced TGF-β1 protein levels. Noticeably, the loss-function of circANKS1B restrained OSCC cell invasion, migration, and epithelial to mesenchymal transition (EMT) by decreasing N-cadherin expression and enhancing E-cadherin expression. Furthermore, the knockdown of circANKS1B sensitized OSCC cells to cisplatin by suppressing cell viability and increasing cell apoptosis and caspase-3 activity. Mechanically, bioinformation software (circinteractome and starBase 3.0) and dual-luciferase reporter assays corroborated that circANKS1B could sponge miR-515-5p. Moreover, miR-515-5p could directly target TGF-β1 to suppress its expression. Importantly, inhibition of miR-515-5p or supplementation with TGF-β1 overturned the effects of circANKS1B knockdown on cell invasion, migration, and cisplatin resistance. Thus, these findings highlight that circANKS1B might act as an oncogenic gene to facilitate the metastatic potential and cisplatin resistance in OSCC by sponging miR-515-5p to regulate TGF-β1. Collectively, circANKS1B may be a promising target for therapy and overcoming chemoresistance in OSCC.